Representation of developing countries in the audiovisual journalism: Unique discourse in the Spanish generalist television channels - Aparicio González, Daniel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of this article is to analyse the image of developing countries (according to the UN classification) offered by Spanish television news programmes. The main methodology is the content analysis, which is developed by the Observatory for the Quality of Information on Television (OCITV), a project of “Universidad Complutense de Madrid”. 70 countries are analysed in a 117 news programmes sample of the five main channels: TVE, Antena 3, Telecinco, Cuatro and La Sexta(2017- 2020). The results prove that these countries are mainly shown with a negative image and framing linked to catastrophes, terrorism and war conflicts.